Asymbiotic Seed Germination and In Vitro Propagation of the Thai Rare Orchid Species; Eulophia bicallosa (D.Don) P.F.Hunt & Summerh. - Thanakorn Wongsa; Jittra Piapukiew; Kanlaya Kuenkaew; Chatchaya Somsanook; Onrut Sapatee; Julaluk Linjikao; Boworn Kunakhonnuruk; Anupan Kongbangkerd (Plants)
An efficient in vitro propagation protocol for Eulophia bicallosa was developed using asymbiotic seed germination and protocorm proliferation. The effect of light on seed germination and development was evaluated on Vacin and Went (VW) medium under five conditions: darkness, white, green, red, and blue light for 24 weeks. Blue and red light significantly accelerated seed development, allowing progression to stage 5 within 24 weeks. For protocorm proliferation, six semi-solid culture media were tested. Half-strength Murashige and Skoog (½MS) medium yielded the best results after 8 weeks, producing the highest numbers of shoots (1.0), leaves (1.1), and roots (4.2) per protocorm, with 100% survival. The effects of organic additives were also evaluated using coconut water and potato extract. A combination of 200 mL L−1 coconut water and 50 g L−1 potato extract enhanced shoot formation (1.7 shoots), while 150 mL L−1 coconut water with 50 g L−1 potato extract increased both leaf (1.9) and root (8.8) numbers. The effects of cytokinins (benzyladenine (BA), kinetin (6-furfurylaminopurine), and thidiazuron (TDZ)) and auxins (indole-3-acetic acid (IAA), α-naphthalene acetic acid (NAA), indole-3-butyric acid (IBA), and 2,4-dichlorophenoxyacetic acid (2,4-D)) were investigated using ½MS medium supplemented with each plant growth regulator individually at concentrations of 0, 0.1, 0.5, 1.0, and 2.0 mg L−1. Among the cytokinins, 0.1 mg L−1 BA produced the highest survival rate (96%), while 1.0 mg L−1 BA induced the greatest shoot formation (93%, 2.3 shoots). Among the auxins, 0.1 mg L−1 IAA resulted in the highest survival (96%), and 1.0 mg L−1 IAA significantly enhanced root induction (4.2 roots per protocorm). Acclimatization in pots containing a 1:1:1 (v/v) mixture of pumice, sand, and soil resulted in 100% survival. This protocol provides a reliable and effective approach for the mass propagation and ex situ conservation of E. bicallosa.